Effectiveness of Nurse Navigator Program on Emotional Distress and Health Education Impact in Patients with Breast Cancer Undergoing Adjuvant Chemotherapy after Surgery - Rattananade, Rattiya; Utriyaprasit, Ketsarin; Sindhu, Siriorn; Chuthapisith, Suebwong (Nursing Science Journal of Thailand, 2022)
Purpose: The aim of the study was to test the effects of a nurse navigator program on emotional distress and health education impact in postoperative breast cancer patients undergoing adjuvant chemotherapy. Design: A randomized controlled trial. Methods: The sample was composed of 60 postoperative with stage I-II breast cancer patients who came for their first follow-up treatments and had plans for adjuvant chemotherapy. The sample was randomly assigned to an intervention group (31 cases) and a control group (29 cases) by using a computer program. The experimental group received the nurse navigator program in line with the Patient Navigation Model is a patient-centered intervention designed to improve patient experiences and the delivery of cancer care by eliminating barriers to care. Data were collected using the Profile of Mood State (POMs-B Thai) and the Health Education Impacts questionnaires (hei Q). Multivariate Analysis of Variance (MANOVA) was used for statistical analysis. Main findings: The breast cancer patients undergoing adjuvant chemotherapy postoperative who received the nurse navigator program had mean emotional distress scores less than the patients who received a usual care with statistical significance (p = .031). However, no statistically significant difference between two groups on health education impact scores was observed (p = .856). Conclusion and recommendations: Nurse Navigator program can reduce emotional distress in postoperative breast cancer patients undergoing adjuvant chemotherapy. Therefore, the nurse navigator program should be practically implemented in care for this group of population.